Osmotherapy in patients with severe brain trauma - Randy Reina-Rivero; Gustavo Gaitán-Herrera; Aixa Eliana García-García; Amalia Molina-Trujillo; Manuel Alejandro Jaramillo-Acosta; Juliana Paniagua-Aguirre; Alfonso Barón-Sánchez; Antonio Luis Castro-Castro; Mohamed Argüello-Manrique; Michael Gregorio Ortega Sierra (Romanian Neurosurgery, 2022)
Traumatic brain injury is still a major cause of mortality and morbidity in the world and is considered a public health problem that needs to be well attended to. Cerebral oedema due to brain injury compromises the delivery of essential nutrients and alters normal intracranial pressure, whose increase has been shown to be strongly associated with poor neurological outcomes and mortality for patients with head trauma. Intravenous fluids are a fundamental component of trauma care and fluid management influences patient outcomes. Thanks to advances in the research of osmotic agents, mortality has been reduced and there has been greater control in intracranial pressure. The osmotic agents most used for the control of intracranial pressure in patients who have suffered severe brain trauma are mannitol and hypertonic saline. However, in recent years have been studying the benefits that sodium lactate can generate in these cases. It has been found that sodium lactate has generated a greater decrease in intracranial pressure values and lower mortality rates with respect to mannitol and hypertonic saline. This still has been disputed as an application of mannitol, hypertonic saline or sodium lactate for treating patients who have suffered some head trauma. This review aims to show the advantages, disadvantages and recommendations of the different hyperosmolar solutions mentioned previously based on current evidence.